"Alexa, tell me …" - A forensic examination of the Amazon Echo Dot 3 rd Generation - D, Pawlaszczyk; J, Friese; C, Hummert (International Journal of Computer Sciences and Engineering, 2019)
In the recent past, smart speakers and personal assistants like Alexa have been used as evidence in different criminal cases. With more than 6 million Echo devices in 2019 worldwide, there is a good chance for the constantly active devices to record criminal behavior. That is reason enough to take a closer look at the subject. This article discusses different starting points for a forensic investigation of the latest generation of the Echo Dot smart speaker. Therefore, the paper examines three possible aspects for the forensic analysis of the Echo 3 the latest generation of this device. In hardware analysis, the focus is not only on the general examination of the extracted data but also on validating the existing methods for data extraction. A second focus is the cloud-side analysis. Since this type of analysis requires the knowledge of credential data, a client-side analysis will take place too. The last is done because the use of at least one Companion Client is necessary to operate and control Alexa-capable devices. The main findings of this study are presented in this article.